Sikkim State Draft Annual Plan 1987-88 Planning and Development Department Government of Sikkim - Planning Commission (Planning Commission, 1987)
Sikkim's Seventh Five Year Plan which has a total outlay of Rs. 230 crores, represents a very substantial step up in the overall development effort in the State. As compared to the actual expenditure during the Sixth Plan which amounted to Rs. 132 crores , the projected outlay for the period 1985-90 will mean an increase of well over 70 percent. During the first year of the plan the State was able to utilise Rs. 41 crores in all. sectors of development activity and during the 1986-87 period an outlay of Rs. 50 crores has been provided for. This outlay is likely to be more than fully utilised.
Planning and Development Department Government of Sikkim